Conceptualizations of language errors, standards, norms and nativeness in English for research publication purposes: An analysis of journal submission guidelines - McKinley, J; Rose, H (Elsevier, 2018)
Adherence to standards in English for research publication purposes (ERPP) can be a substantial barrier for second language (L2) writers and is an area of renewed debate in L2 writing research. This study presents a qualitative text analysis of author guidelines in 210 leading academic journals across 27 disciplines. It explores conceptualizations of language errors, standards, norms and nativeness in journal submission guidelines, and identifies key concepts related to so-called error-free writing. Findings indicate that most of the journal guidelines are inflexible in their acceptance of variant uses of English. Some guidelines state a requirement of meeting an unclear standard of good English, sometimes described as American or British English. Many guidelines specifically position L2 writers as deficient of native standards, which raises ethical considerations of access to publication in top journals. This study leads to a discussion of a need to re-conceptualize error-free writing in ERPP, and to decouple it from concepts such as nativeness. It focuses on a need to relax some author guidelines to encourage all authors to write using an English that can easily be understood by a broad, heterogeneous, global, and multilingual audience.